2020
DOI: 10.1523/jneurosci.1316-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Mitochondrial Transport Is Essential for Organelle Distribution and Health in Zebrafish Neurons

Abstract: In neurons, mitochondria are transported by molecular motors throughout the cell to form and maintain functional neural connections. These organelles have many critical functions in neurons and are of high interest as their dysfunction is associated with disease. While the mechanics and impact of anterograde mitochondrial movement toward axon terminals are beginning to be understood, the frequency and function of retrograde (cell body directed) mitochondrial transport in neurons are still largely unexplored. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 103 publications
7
45
0
Order By: Relevance
“…This assumption is relaxed in the 'Changing of the Guard' model, where stationary mitochondria can restart in either the anterograde or retrograde direction. The fate of mitochondria when they reach the terminus of an axon may involve some combination of local degradation [60] and recirculation towards the soma [61][62][63]. Given that the retrograde and anterograge flux of mitochondria are similar in axons [32,62,64], we assume that most of the organelles return to the cell body for recycling.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…This assumption is relaxed in the 'Changing of the Guard' model, where stationary mitochondria can restart in either the anterograde or retrograde direction. The fate of mitochondria when they reach the terminus of an axon may involve some combination of local degradation [60] and recirculation towards the soma [61][62][63]. Given that the retrograde and anterograge flux of mitochondria are similar in axons [32,62,64], we assume that most of the organelles return to the cell body for recycling.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…3 b). In actr10 mutants, mitochondria accumulate in the afferent terminals, afferent terminals are swollen, and synaptic function is impaired (Mandal et al 2021 ). Notably, the afferent terminal phenotypes and mitochondrial trafficking defects observed in actr10 mutants may be related to the auditory neuropathy observed in Charcot–Marie–Tooth disease.…”
Section: Main Bodymentioning
confidence: 99%
“…Ref. [30] reported that complete turnover of mitochondria in axon terminals of zebrafish neurons occurs within 24 hours.…”
Section: Estimation Of the Average Age Of Mitochondria In The Most Distal Demand Sitementioning
confidence: 99%